Global logistics strategies delivering the goods - Manners-Bell, John (Kogan Page, 2014)
"Global Logistics Strategies examines how the logistics industry has developed; how it is influenced by macro-economic factors and demand-side trends; what the risks are to the industry and how it will develop over the coming years. The book examines individual logistics segments looking at each one's unique micro-economic dynamics. It explains how logistics companies' revenues and profitability are affected by a downturn, and how this is governed by such factors as whether they own assets or manage them. Six key logistics segments (freight forwarding, contract logistics, shipping, road freight, air cargo and express) are defined, explored and described in detail. The book also examines the individual supply chain dynamics and logistics demands of the major vertical sectors: Automotive, Chemical, Pharmaceutical, Retail, Consumer and High Tech."
Includes bibliographical references and index
Keywords: BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Distribution; BUSINESS & ECONOMICS / Facility Management; Wirtschaft; Physical distribution of goods; Business logistics -- Management; Distributionslogistik; Distribution -- Physische Distribution